Aplikasi Sistem Pembayaran Administrasi Sekolah Berbasis Web di SMPI Nurush Shodiqin - Amelia Putri; Misnawati Misnawati; Yudi Setiawan; Wasis Haryono (Asosiasi Riset Ilmu Matematika dan Sains Indonesia, 2025)
An effective school payment system will trigger the performance of the agency to be better than before. Web-Based School Administration Payment System Application at SMPI Nurush Shodiqin, In the world of education, an efficient and integrated administration system is very important to maintain the smooth running of academic and management processes, including data management of students, teachers, and school management. Nurush Shodiqin Islamic Junior High School (SMPI), as one of the educational institutions in the region, experiences problems in administrative management. The administration system used is still manual, especially in terms of recording student data, recapitulating grades, and paying tuition fees. This causes various problems such as data input errors, loss of important records, and delays in delivering information to related parties. . Therefore, the implementation of a Web-based Administration System at SMPI Nurush Shodiqin is a relevant solution. This system is expected to be able to overcome existing problems and improve the quality of school administration services. With a web-based system, it is expected that the administration process can be carried out more quickly, accurately, and transparently.